Analisis Tingkat Ketertarikan Mahasiswa Terhadap Bidang Artifcial Intelligence dalam Penulisan Skripsi dengan Random Forest - Anshor, Abdul Halim; Wiyatno, Tri Ngudi (Forum Kerjasama Pendidikan Tinggi, 2024)
Artificial Intelligence (AI) is an advanced phenomenon of information technology that is currently very fast. With AI human work can be replaced by computers. Universities are superior providers in providing experts in the field of AI. One indicator that can describe how the curriculum in the field of AI is implemented on campus is by assessing how interested students are in taking the field of AI for writing their thesis. In this research, researchers used the Random Forest machine learning method with questionnaire sampling data from 200 students interested and not interested in the field of AI. The results of this research will provide accuracy values for classifying students' interest in the field of AI. Questionnaire data will be classified into two classes, namely interested and not interested classes. Results from classification trials with the WEKA application. It is known that the classification results have an accuracy value of 80.5%, this shows that the random forest algorithm has worked effectively in the process of classifying Pelita Bangsa University student interest data in the field of AI in writing theses